2017
DOI: 10.1038/s41598-017-03773-y
|View full text |Cite
|
Sign up to set email alerts
|

Hair bundles of cochlear outer hair cells are shaped to minimize their fluid-dynamic resistance

Abstract: The mammalian sense of hearing relies on two types of sensory cells: inner hair cells transmit the auditory stimulus to the brain, while outer hair cells mechanically modulate the stimulus through active feedback. Stimulation of a hair cell is mediated by displacements of its mechanosensitive hair bundle which protrudes from the apical surface of the cell into a narrow fluid-filled space between reticular lamina and tectorial membrane. While hair bundles of inner hair cells are of linear shape, those of outer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…While regional (apex, middle, or base) variations are hypothesized to enhance frequency-specific hearing (Kielczynski, 2017 ), data are mostly correlative. To date, for example, no studies have changed local HC variation to make basal HCs as long as their apical counterparts, or vice versa, in part because we are only beginning to understand the mechanisms of this local variation (Ciganović et al, 2017 ). Longitudinal HC variations seems to translate a temporal variation of differentiation, starting with Atoh1 expression near the base, relative to cell cycle exit, starting at the apex, to generate spatial cell-type variations (Kopecky et al, 2013 ; Yizhar-Barnea and Avraham, 2017 ).…”
Section: Organization Of the Adult Mammalian Organ Of Cortimentioning
confidence: 99%
“…While regional (apex, middle, or base) variations are hypothesized to enhance frequency-specific hearing (Kielczynski, 2017 ), data are mostly correlative. To date, for example, no studies have changed local HC variation to make basal HCs as long as their apical counterparts, or vice versa, in part because we are only beginning to understand the mechanisms of this local variation (Ciganović et al, 2017 ). Longitudinal HC variations seems to translate a temporal variation of differentiation, starting with Atoh1 expression near the base, relative to cell cycle exit, starting at the apex, to generate spatial cell-type variations (Kopecky et al, 2013 ; Yizhar-Barnea and Avraham, 2017 ).…”
Section: Organization Of the Adult Mammalian Organ Of Cortimentioning
confidence: 99%
“…We observed consistently that row 1 and row 2 stereocilia have insertion positions with a central column shifted forward, creating a notch in the hair bundle. When imaging the hair bundle with intact stereocilia using SEM, the IHC insertion pattern is not evident, which explains why the stereociliary arrangements of rows 1 and 2 in IHCs have been described as forming an almost straight line ( Engström and Engström, 1978 ; Forge et al, 1988 ; Ciganović et al, 2017 ). Two reports describe a “W” shape caused by the notch in adult chinchilla and guinea pig, although the insertion positions are not visible ( Lim, 1986 ; Furness and Hackney, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…The dynamics of this system occur at low Reynolds number, 35 and we have previously shown that the drag of the artificial membranes is small in comparison to that of the entire coupled system. 23 Further, the mica flakes exhibit little compliance, as we observe coupling and synchronization between pairs of hair bundles with large spacial separation.…”
Section: Numerical Model Of Coupled Hair Cellsmentioning
confidence: 96%